Penerapan Algoritme Kriptografi RC6 Untuk Mengamankan File Penjualan Dan Gambar Produk Alisan - Siswanto, Siswanto; Basuki Hari Prasetyo; M. Anif; Ari Saputro; Subandi; Djati Kusdiarto; Izzah Fadhilah Akmaliah (Ikatan Ahli Informatika Indonesia, 2023)
Problems that commonly occurred in this period were that the sales data for Alisan products in several stores was falsified and there were quite large differences that did not match the reported data, as well as the large number of fake product images which could damage the image of the original Alisan products. One of the main problems faced in developing e-commerce web applications is the vulnerability of sales data and product images to security threats, such as hacking and data theft. The aim of this research is to create an application that implements the RC6 encryption algorithm to protect web-based Alisan product sales files and product images. This research aims to fill this gap by focusing on the effectiveness of the Rivest Code 6 (RC6) algorithm in protecting critical transactional and visual data in an e-commerce context. In addition, this research examines the impact of RC6 implementation on system performance and compares it with other encryption methods commonly used in web applications. Therefore, this research is expected to provide valuable insights for stakeholders in developing better data security solutions for web-based businesses. Applications are evaluated and planned with user acceptance testing (UAT). The results of application testing showed that the average size of the encryption process was 146,878.6 bytes and the processing time was 3.576291 MS and the average size of the decryption process was 146,854.6 bytes and the processing time was 2.8220591 MS. Test results from 26 UAT respondents, 89.1% agreed that the entire implementation of the RC6 algorithm can be used by Alisan employees to protect sales report files and Alisan product image files easily and safely.